2001
DOI: 10.1034/j.1600-0420.2001.079004408.x
|View full text |Cite
|
Sign up to set email alerts
|

Ocular and orbital cysticercosis

Abstract: ABSTRACT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
123
0
5

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(133 citation statements)
references
References 20 publications
(27 reference statements)
2
123
0
5
Order By: Relevance
“…Ocular and extra ocular cysticercosis is world wide in distribution and series of the cases have been reported from India [2][3][4][5][6]. The patients may be asymptomatic in early stage of the disease but it results in gradual loss of vision with or without pain, depending upon the location of the lodged larva.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ocular and extra ocular cysticercosis is world wide in distribution and series of the cases have been reported from India [2][3][4][5][6]. The patients may be asymptomatic in early stage of the disease but it results in gradual loss of vision with or without pain, depending upon the location of the lodged larva.…”
Section: Discussionmentioning
confidence: 99%
“…Intra orbital and intra ocular cysticercosis are however uncommon as compared to involvement of neural and muscle tissue [1]. The commonest clinical presentation is subconjunctival cyst or proptosis in patients, mostly from poor socioeconomic status [2,4]. In most studies higher incidence of orbital cysticercosis is reported in first two decades of life with male predominance [3,6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other endemic areas include Mexico, Latin America, China, Indonesia and Eastern Europe. 6 In India, 78% of the cases with ocular cysticercosis have been reported from states of Andhra Pradesh and Pondicherry. 7,8 Cysticercosis may cause significant visual loss, especially if the cyst is located intraocularly or is compressing the optic nerve.…”
Section: Prevalencementioning
confidence: 99%
“…Because of its constant motility it may erodes through the conjunctiva and comes out leaving a rent in the conjunctiva which ultimately heals within a short period. 6,21,22 Extraocular myocysticercosis :-Cysticercosis of extraocular mucle usually presents as recurrent pain, redness, proptosis, ocular motility restriction, diplopia and ptosis. 23,24 One or more extraocular muscles may be simultaneously involved, although a propensity for involvement of the superior muscle complex and the lateral rectus muscles has been reported.…”
Section: Clinical Presentationmentioning
confidence: 99%